2005
DOI: 10.2174/1389450054863671
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in Acute Myelogenous Leukaemia (AML): Methodological Strategies and Identification of Protein Targets for Novel Antileukaemic Therapy

Abstract: Enduring efforts into determination of the molecular biological status of acute myelogenous leukaemia (AML), a stem cell disease characterised by distinct blastic differentiation blocks and their extensive growth, continue to provide us with prognostically important information for more than half of all patients. In subsets of AML, molecular diagnostics rigorously guide the clinician toward the choice of optimal therapy. The in-depth characterization of leukemogenesis associated genetic alterations, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…A constant challenge is therefore to offer effective therapy to the older patients where low toxicity therapy is needed to obtain disease control (6 -8). The development of molecular targeted therapy with attenuated toxicity may be the most effective way of obtaining increased overall survival for AML patients (9,10).…”
mentioning
confidence: 99%
“…A constant challenge is therefore to offer effective therapy to the older patients where low toxicity therapy is needed to obtain disease control (6 -8). The development of molecular targeted therapy with attenuated toxicity may be the most effective way of obtaining increased overall survival for AML patients (9,10).…”
mentioning
confidence: 99%
“…For example, Hu et al (54) found that heat shock protein 70 was up-regulated in ovarian cancer cell lines using SELDI-TOF-MS, and treatment with a heat shock protein 70 inhibitor stunted growth of the cell line (54). Similar studies in vitro and in mouse models have been performed in other malignancies, including acute lymphoblastic leukemia, acute myeloid leukemia, colon cancer, hepatocellular carcinoma, and breast cancer (55)(56)(57)(58).…”
Section: Clinical Applications Of Functional Proteomicsmentioning
confidence: 59%
“…To date, image based methods used for assessing and quantifying epigenetic changes include electron microscopy (Hendzel et al, 1998;Khorasanizadeh, 2004), image correlation spectroscopy (Fejes Toth et al, 2004;Gorisch et al, 2005), confocal imaging and flow cytometry (Le Beyec et al, 2007), high resolution texture analysis of chromatin phenotype (Mohamed et al, 2007), in situ localisation methods (Tumbar et al, 1999;Verschure et al, 1999), protein chromatin interaction studies (Musri et al, 2006;Padilla-Parra et al, 2008) which in some instances include complex proteomics based analysis (Sjoholt et al, 2005) or can be coupled to nucleosomal arrays (Sous et al, 2004). In light of these methods, which each have their obvious advantages the main benefit of the method proposed in this article, is its simplicity.…”
Section: Introductionmentioning
confidence: 99%